Digitalisasi Pendidikan Pesantren: Penerapan Teknologi Dan Dampaknya - Mohammad Solihin; Sholihan (Global Action and Education for Society, 2025)
The digitization of pesantren education is an effort toward modernization and digital transformation aimed at enhancing the effectiveness of religious learning without eliminating traditional values. This study discusses the implementation of education at Darul Lughah Wal Karomah pesantren through the use of digital technology, the challenges of digitizing pesantren education, and its resulting impacts. Using a qualitative approach, this research combines documentation and interviews with pesantren administrators, teachers, and students, as well as a review of relevant literature. The findings show that the digitization of pesantren education brings many benefits, including easier access to learning materials and greater flexibility in the teaching process. However, it also presents challenges, such as limited human resources and the potential shift in traditional values.